Characterization of plastic scintillator bars using fast neutrons from D-D and D-T reactions. (11th August 2021) - Dey, R.; Netrakanti, P.K.; Mishra, D.K.; Behera, S.P.; Mulmule, D.; Patel, T.; Sarkar, P.S.; Jha, V.; Pant, L.M.
Abstract: We report results of fast neutron response in plastic scintillator (PS) bars from deuterium-deuterium ( D - D ) and deuterium-tritium ( D - T ) reactions using Purnima Neutron Generator Facility, BARC, Mumbai. These measurements are useful in context of Indian Scintillator Matrix for Reactor Anti-Neutrino (ISMRAN) detection, an array of 10×10 PS bars, used to measure reactor anti-neutrinos through inverse beta decay (IBD) signal. ISMRAN detector, an above-ground experiment close to the reactor core (∼13m), deals with an active fast neutron background inside the reactor hall. A good understanding of fast neutron response in PS bars is an essential pre-requisite for suppression and discrimination of fast neutron background from IBD events. A monoenergetic neutron beam from the fusion reaction of D - D at 2.45 MeV and D - T at 14.1 MeV are used to characterize the energy response in these bars. The neutron energy response function has been simulated using the GEANT4 package and are compared with the measured data. A reasonable agreement of deposited energies by fast neutrons in PS bars between data and simulation are obtained for these reactions. The ratio of energy deposition in adjacent bars is used to discriminate between prompt IBD, fast neutron and neutron capture cascade gamma events.